STUDI KELAYAKAN WAKAF PRODUKTIF - Aji, Gunawan (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2015)
AbstractMosque as one of the objects of waqf can provide added value if managed productively. Land of the mosque can be used for a variety productive activities according to the principles of Islam. ! is study analyzes the aspects of marketing and " nancial aspects, the feasibility study for the project productive endowments shopping block Masjid AlFairuz Pekalongan.The data used in the form of quantitative and qualitative data. Factors that will be analyzed in the marketing aspects that shape the market, demand and supply, marketing strategy (segmenting, targetting, and positioning), as well as the marketing mix strategy.Financial aspects of the Average Rate of Return, Payback Period, Net Present Value, Internal Rate of Return , and Pro" tability Index. The results of research projects developing productive waqf shopping block mosque of Al-Fairuz Pekalongan is feasible. In the aspect of marketing, business managers haveestablished a marketing strategy and marketing mix well. On the " nancial aspect, the ARR value indicates the number of 59%, greater than the minimum accounting rate of return of 7.30%. Payback Period calculation produces a value of 2 years, 6 months, 29 days, less than the economic life of the project. Project NPV is positive value of Rp 209,224,199.00. IRR of 20%, greater than the rate of return of deposits mudaraba Islamic banks are used in the calculation (7.30%). PI calculation results show 1.297193465 value greater than 1 (PI > 1) .Keywords: Feasibility Study, Waqf Productive, marketing aspects, " nancial aspects